2021
DOI: 10.1155/2021/9306532
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Effectiveness and Safety between Intraoperative 3D-CT-Guided and C-Arm-Guided Percutaneous Balloon Compression for Idiopathic Trigeminal Neuralgia:  A  Multi-Center Retrospective Study

Abstract: Objectives. To compare 3D-CT-guided and C-arm-guided percutaneous balloon compression (PBC) in terms of effectiveness and safety. Methods. The medical records and follow-up data of patients with idiopathic trigeminal neuralgia who underwent 3D-CT-guided or C-arm-guided PBCs in Beijing Tiantan Hospital and the Characteristic Medical Center of the Chinese People’s Armed Police Force between February 2018 and March 2020 were retrospectively reviewed and analysed. Results. A total of 291 patients were included. Am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…The use of Dyna-CT-assisted PMC has a low incidence of complications and a good prognosis. Xiao et al ( 14 ) reported the comparison of CT-guided and C-arm guided PMC surgery. The 3D-CT group required less time than the C-arm group for puncture ( p < 0.001) and for the whole operation ( p < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…The use of Dyna-CT-assisted PMC has a low incidence of complications and a good prognosis. Xiao et al ( 14 ) reported the comparison of CT-guided and C-arm guided PMC surgery. The 3D-CT group required less time than the C-arm group for puncture ( p < 0.001) and for the whole operation ( p < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Among these options, a large number of researches have been carried on initial TN, recurrent TN after MVD, or TN secondary to multiple sclerosis (MS) using percutaneous balloon compression (PBC). [10][11][12] A STROBE-compliant study showed that immediate pain relief after PBC was 98.6% (Barrow Neurological Institute [BNI] classes I, II); the pain cure rates at 1, 2, 3, 4, and 5 years were 93.5%, 90.4%, 84.7%, 80.4%, and 72.9%, respectively. 13 In addition, radiofrequency thermocoagulation (RFT) has been widely applied in elderly patients with classic or idiopathic TN, or patients with recurrent TN after MVD as well as other neurosurgeries and some patients with secondary TN who are unwilling to accept a more invasive approach.…”
Section: Introductionmentioning
confidence: 99%
“…If MVD is not an option due to the risk of surgery and general anesthesia, many pain surgeons prefer to select a less‐invasive neurosurgical intervention. Among these options, a large number of researches have been carried on initial TN, recurrent TN after MVD, or TN secondary to multiple sclerosis (MS) using percutaneous balloon compression (PBC) 10–12 . A STROBE‐compliant study showed that immediate pain relief after PBC was 98.6% (Barrow Neurological Institute [BNI] classes I, II); the pain cure rates at 1, 2, 3, 4, and 5 years were 93.5%, 90.4%, 84.7%, 80.4%, and 72.9%, respectively 13 .…”
Section: Introductionmentioning
confidence: 99%
“…We processed digital imaging and communications in medicine (DICOM) data to preoperatively reconstruct 3D images using the software 3D-Slicer ( 15 – 17 ), and then observed the relationship between nerves and peripheral blood vessels more intuitively and accurately, measured the shape and volume of the Meckel cavity, observed the shape of the FO, and simulated the puncture of the FO. During the operation, Dyna CT ( 18 , 19 ) was used to scan and make 3D model of the skull, and FO puncture was performed with the assistance of dynamic X-ray fluoroscopy and 3D model navigation. Using Dyna CT, the position and shape of metallic hollow introducer, catheter and balloon were observed in real time, and could be adjusted at any time.…”
Section: Introductionmentioning
confidence: 99%